2018
DOI: 10.1111/ijpo.12492
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent body composition and associations with body size and growth from birth to late adolescence. The Tromsø study: Fit Futures—A Norwegian longitudinal cohort study

Abstract: Summary Background Fat and fat‐free masses and fat distribution are related to cardiometabolic risk. Objectives: to explore how birth weight, childhood body mass index (BMI) and BMI gain were related to adolescent body composition and central obesity. Methods In a population‐based longitudinal study, body composition was measured by dual‐energy X‐ray absorptiometry in 907 Norwegian adolescents (48% girls). Associations between birth weight, BMI categories, and BMI gain were evaluated by fitting linear mixed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 50 publications
(116 reference statements)
1
17
0
2
Order By: Relevance
“…Agreement between cluster assignments (i.e., low, middle, or high) using AGE5 or ALL data was good for BMI and each body composition measure, suggesting that one’s BMI and relative distribution of % BF, FMI, and FFMI are established during early childhood and remain stable throughout adolescence. These data are consistent with observations that children having high BMIs during childhood are at increased risk of obesity during adolescence and adulthood [ 20 , 21 , 22 , 23 ]. Simmonds et al conducted a systematic review and meta-analyses to investigate the persistence of obesity from childhood into adulthood, and reported a strong positive association between a high childhood BMI and adult obesity [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Agreement between cluster assignments (i.e., low, middle, or high) using AGE5 or ALL data was good for BMI and each body composition measure, suggesting that one’s BMI and relative distribution of % BF, FMI, and FFMI are established during early childhood and remain stable throughout adolescence. These data are consistent with observations that children having high BMIs during childhood are at increased risk of obesity during adolescence and adulthood [ 20 , 21 , 22 , 23 ]. Simmonds et al conducted a systematic review and meta-analyses to investigate the persistence of obesity from childhood into adulthood, and reported a strong positive association between a high childhood BMI and adult obesity [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Using growth data from German children recorded in the CrescNet patient registry, Geserick et al found that preschool children with high acceleration in annual BMI increments were 1.4 times as likely to be overweight or obese during adolescence as their peers with stable preschool BMIs [ 22 ]. Evensen et al reported that high BMIs during early childhood predicted higher fat mass during late adolescence [ 23 ]. These findings extend previous BMI findings by documenting that % BF, FMI, and LMI also track within individuals throughout childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, after adjusting for body fat, trunk fat was lower in children born LGA 15 . Born LGA showed no association with central overweight/obesity, 21 whereas LGA‐born children were at a lower risk of metabolic syndrome 16 . A significant association of increased body fat accumulation and infant peak weight velocity was found, but that was evident in both LGA and non‐LGA infants 27,40 .…”
Section: Resultsmentioning
confidence: 90%
“…The studies were published between 1993 and 2019, with a total of 39 501 participants. Eight studies had sample sizes greater than 500, 18–21,23,26,27,30,40 and 11 studies had sample sizes smaller than 100 participants 17,19,24,25,28,29,37,39,42–44 . Six studies used population sample from Spain, 14,19,24,25,34,43 five from the USA, 17,18,31,39,42 three studies each from Italy, 16,22,35 France 15,28,38 and the Netherlands, 23,27,40 two studies each from Sweden 29,32 and Turkey, 41,44 one study each from Australia, 20 Belarus, 26 Chile, 37 Denmark, 30 Finland, 33 Germany 36 and Norway 21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation